Health Literacy and Health Outcomes in Chronic Obstructive Pulmonary Disease Patients: An Explorative Study - Deniz Azkan Ture; Sudip Bhattacharya; Hakan Demirci; Tekin Yildiz (Frontiers Media S.A., 2022)
AimThis study aimed to evaluate the relationship between health literacy (HL) and chronic obstructive pulmonary disease (COPD) severity.MethodsPulmonary function test, sociodemographic features, Modified Medical Research Council (mMRC) dyspnea scale, COPD assessment test (CAT), and the European Health Literacy Survey Questionnaire were used. The study examined 13,760 patients who underwent a pulmonary function test. Out of 13,760 patients, 673 patients had FEV1/FVC values less than 70%. Those with FEV1/FVC< 0.70 (n = 336) after the reversibility test were included in the study.ResultsThere was a significant decrease in HL and an increase in COPD severity (p < 0.001). In multivariate analysis, the risk of severe COPD was 2.74 times higher in patients in the poor income level than in patients in the good income level. In patients with inadequate HL, the risk of developing severe COPD was 1.80 times higher. A significant difference was found in HL index scores among the groups in terms of education level and income level (p < 0.001; p < 0.001, respectively). The most difficult topics for patients with COPD were periodic health examinations, good practices in mental health, and adult vaccinations.ConclusionsPatients with COPD were found to be at a HL level well below the expected level. The risk of severe COPD increased with poor income and inadequate HL. Healthcare providers should be careful in accessing, understanding, and interpreting the health information of patients with inadequate HL. Therefore, patient education should be prioritized in the follow-up and in the treatment of patients with COPD. Physicians should pay maximum attention to patients with COPD in the regular use of drugs, their proper use, in taking preventive measures, and in adult vaccination.